TINJAUAN YURIDIS KAUSULA ASURANSI JIWA KREDIT TERHADAP PERJANJIAN KREDIT DI BANK - Wijaya, Anton; Svinarky, Irene (SCIENTIA JOURNAL, 2021)
This study aims to determine clearly how to application of the law to the parties who hace included a credit life insurance clause in the credit agreement with the bank. Based on the results of the research that the authors get, it can be concluded that in credit life insurance we know 3 (three) main parties that is the insurer (insurance company), the insured (debtor who bears his life), heirs. Life insurance which is an example of insurance with a certain cost where risk reimbursement will not be in accordance with risks experienced. Death is an event in life insurance. Which creates rights and obligations for the parties. In general, when the insured dies, the insurer has an obligation to provide compensation to the beneficiary (heirs) unless otherwise agreed. For the example, the debtor agrees to clause given by the bank, containing cooperation with the life insurance company to overcome the risks that occur. So in this case the bank acts as a policyholder (recipient) of the compensation.